Association between community empowerment and malaria prevention behaviors among communities in the Working Area of Iwur Public Health Center - Januarius Utimkesan; Yuly Peristiowati; Ratna Wardani (Politeknik Negeri Subang, 2026)
Background: Malaria remains a major public health challenge in remote Indonesian regions like Iwur due to limited healthcare access. Persistent transmission is driven by low community awareness, poor environmental management, and inadequate preventive practices. Community empowerment offers a sustainable strategy to enhance local engagement and strengthen local capacity. An innovative empowerment model is essential at Iwur Public Health Center (Puskesmas Iwur) to optimize prevention efforts and reduce the disease burden. Purpose: This study aimed to develop and evaluate the effectiveness of a Community Empowerment Model for malaria prevention in the Iwur Public Health Center working area. Methods: A quantitative cross-sectional study was conducted among community members in malaria-endemic villages within the Puskesmas Iwur working area. Participants were selected using purposive sampling. Data were collected using a structured questionnaire assessing community empowerment and malaria prevention behaviors. Descriptive statistics and Pearson correlation analysis were performed to examine the association between community empowerment and malaria prevention behavior, with statistical significance set at p < 0.05. Results: The findings showed a statistically significant positive correlation between community empowerment and malaria prevention behavior (r= 0.58, p < 0.001). Higher levels of community empowerment were associated with better malaria prevention practices among community members, suggesting that community participation, health literacy, and self-reliance are important factors associated with malaria prevention in endemic areas. Conclusion: The Community Empowerment Model effectively strengthens community participation and malaria prevention practices. Integrating empowerment-based interventions into primary healthcare programs is recommended to support sustainable malaria control and reduce incidence in endemic communities.